How do protected landscapes associated with high biodiversity and population levels change? - Cuenca, Pablo (2017)
Most protected areas (PA) try to limit logging of forests by means of restrictions on access and use, especially in areas where local communities coexist with the forests and depend on resources derived from PAs. In such contexts, achieving full or effective protection of the forests is almost impossible. This fact has led to researching beyond PAs boundaries in order to examine large surrounding landscapes with multiple forms of properties and restriction on forests use. The present study assessed the change in forest cover and fragmentation between 1990 and 2014, in addition to the drivers that explain such changes in a landscape with the presence of PAs and high-density population belonging to the Chocó-Darien biodiversity hotspot. Results indicated differences in the extent and spatial patterns of change in forest cover of PAs and their surrounding landscapes. Two PAs exhibited a tendency to increase fragmentation and lose their forests in comparison with the stable protection of the forests in other PAs during this period. However, the greatest change in forest cover and fragmentation was observed in the surrounding landscapes, where the best connection to markets and transport networks were the dominating deforestation drivers. Our findings corroborated that the PAs were a shield against the deforestation of the tropical Andean forest, especially in landscapes with high-density population. However, the fragmentation of the forest cannot be avoided around the PAs limits. It is expected that, if this tendency continues in the future, the biodiversity in the Chocó-Darien hotspot will be seriously affected.